2015
DOI: 10.1089/end.2015.0353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Improved Urinary Peak Flow Rates After Robot-Assisted Radical Prostatectomy

Abstract: The natural history of prostatic obstruction for men 40 to 80 years typically reveals reduction of mean PFRs. We observed that removal of the prostate resulted on average with a near doubling of PFRs and decreased PVRs (>50%) by 3 months. After RARP, the average PFR was reset to 25-30 mL/s, and these results were seen across all age, LUTS, and prostate weight groups; the gains remained stable 2 to 4 years after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Skarecky et al reported that the maximum flow rate on uroflowmetry improved significantly after RARP. [ 25 ] As just described, it is generally considered that the maximum flow rate after radical prostatectomy would be improved by removing the bladder outlet obstruction. The reason why the maximum flow rate was not significantly improved in the present study is that the true result might have been masked by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Skarecky et al reported that the maximum flow rate on uroflowmetry improved significantly after RARP. [ 25 ] As just described, it is generally considered that the maximum flow rate after radical prostatectomy would be improved by removing the bladder outlet obstruction. The reason why the maximum flow rate was not significantly improved in the present study is that the true result might have been masked by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…21,28 RARP additionally contributes to improved urinary peak flow rates across all 3 LUTS groups. 29 Men who choose an active monitoring protocol, radiation, 30 or hormonal therapies remain at risk for declining urinary function in the form of reduced daily QOL and the subsequent risk of treatment by transurethral resection of the prostate or chronic α-blocker therapy. These findings should be shared with prostate cancer patients whose LUTS already have a negative impact on their daily QOL.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, limited studies have evaluated UF after radical prostatectomy (RP) . Previously, we reported a doubling of PFR and a >50% reduction in PVR after open and robot‐assisted radical prostatectomy (RARP), both of which were stable with long‐term follow‐up across all age groups . The aim of the present study was primarily to evaluate whether there were significant improvements in PFR from baseline after RARP in men at risk of BOO, similar to those in men without BOO, and whether the improvements persist over long‐term follow up .…”
Section: Introductionmentioning
confidence: 91%
“…[5][6][7][8] Previously, we reported a doubling of PFR and a >50% reduction in PVR after open and robot-assisted radical prostatectomy (RARP), both of which were stable with long-term follow-up across all age groups. 9,10 The aim of the present study was primarily to evaluate whether there were significant improvements in PFR from baseline after RARP in men at risk of BOO, similar to those in men without BOO, and whether the improvements persist over long-term follow up. 10 Finally, because several reports have found an association between BOO and nerve growth factor (NGF), [11][12][13] we explored whether this relationship resulted in a more aggressive prostate cancer.…”
Section: Introductionmentioning
confidence: 99%